Public Procurement in the Informal Economy’s Structure - GRISHMANOVSKII, DENIS YURIEVICH; SAMOLYSOV, PAVEL VALERIEVICH; TSVILIY-BUKLANOVA, ANNA ALEKSANDROVNA; RUSANOV, MIKHAIL SERGEYEVICH; PAVLICHENKO, NIKOLAI VLADIMIROVCH (The journal of contemporary issues in business and government, 2020)
Abstract: The issue of a large part of informal economy in the public procurement sphere should bу investigated comprehensively. There is a number of problems, which evolve from the informal economy, that is why there is a need for certain reforms. An effective contract system is to be created with the help of a systematic approach to the implementation of such reforms. A set of efficient measures aimed at improving the pricing methodology and contract execution quality will allow reducing the volume of informal economy in public procurement what will promote the national economic security.